2018
DOI: 10.1111/jgs.15468
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Physical Function As a Predictor of Hospitalization in the Lifestyle Interventions and Independence for Elders Study

Abstract: Background Hospitalization reduces mobility for many older adults, which in turn is associated with an increased risk of hospitalization. Physical function screening may identify an at-risk population for intervention. The Mobility Assessment Tool – short form (MAT-sf) is a brief, animated, computer-based means of assessing mobility that predicts mobility disability. This study explored whether baseline MAT-sf scores are associated with number of hospitalizations and time to first hospitalization across a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In older people, there is strong evidence of a positive effect from regular physical activity on lower limb physical functioning, 7 , 8 the ability to live independently in the community, reduced hospital admissions, and mortality. 9 , 10 Despite these substantial benefits, people become less physically active and more sedentary as they age, with only 12% of UK adults aged 65 years and older meeting UK physical activity guidelines. 11 Sedentary behaviours are even more prevalent in socioeconomically deprived parts of the population, 12 which is a key driver of health inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…In older people, there is strong evidence of a positive effect from regular physical activity on lower limb physical functioning, 7 , 8 the ability to live independently in the community, reduced hospital admissions, and mortality. 9 , 10 Despite these substantial benefits, people become less physically active and more sedentary as they age, with only 12% of UK adults aged 65 years and older meeting UK physical activity guidelines. 11 Sedentary behaviours are even more prevalent in socioeconomically deprived parts of the population, 12 which is a key driver of health inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigated the effect of a MI task on the overall brain network using graph theory network analyses. The MI tasks employed items from the MAT-sf, a motor imagery task where performance is associated with major objective tests of mobility and predicts clinical outcomes, including major mobility disability [ 21 , 22 , 23 , 24 ]. We found that, when compared to the resting state, global community structure consistency declined during the MI tasks and with increased difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…The MAT-sf is a brief, self-report tool with 10 animated video clips illustrating common mobility tasks [ 21 , 22 , 23 ]. It is correlated with major objective tests of physical function and has been found to predict outcomes following surgery and major mobility disability [ 16 , 22 , 23 , 24 ]. In the present study, we utilize a variation of the MAT-sf adapted for use in the scanner in which two videos are shown to participants that include relatively easy and more difficult motor tasks, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Every individual has a desire to move forward, but some people have obstacles to that desire to move forward. A person tends to feel that the expectations possessed are difficult to realize, overthinking the difficulty and overthinking people's views (Callahan, 2018). Negative thinking will be very detrimental.…”
Section: Introductionmentioning
confidence: 99%